2009
DOI: 10.1080/10673220902996775
|View full text |Cite
|
Sign up to set email alerts
|

Differential Patterns of HPA Activity and Reactivity in Adult Posttraumatic Stress Disorder and Major Depressive Disorder

Abstract: Despite a number of overlapping symptoms, individuals with posttraumatic stress disorder (PTSD) and major depressive disorder (MDD) often display hypothalamic-pituitary-adrenal (HPA) profiles that appear quite different from one another. This review describes the patterns of HPA-axis activity and reactivity in healthy individuals compared to individuals with these two disorders. Measures of HPA-axis activity and reactivity include cortisol levels at rest, in response to the dexamethasone suppression test (DST)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
48
0
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 103 publications
(52 citation statements)
references
References 113 publications
(116 reference statements)
3
48
0
1
Order By: Relevance
“…This is called the Hypothalamu-Pituitary-Adrenal (HPA) axis. Cortisol is a reliable indicator of HPA axis functioning and it is well established that cortisol levels are higher among depressed individuals [12,59]. However, research examining the effects of exercise on cortisol in the general population and among depressed individuals is equivocal to date [60,61].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This is called the Hypothalamu-Pituitary-Adrenal (HPA) axis. Cortisol is a reliable indicator of HPA axis functioning and it is well established that cortisol levels are higher among depressed individuals [12,59]. However, research examining the effects of exercise on cortisol in the general population and among depressed individuals is equivocal to date [60,61].…”
Section: Discussionmentioning
confidence: 99%
“…However, the prevalence rates of PPD may be underestimated as depressive symptoms show a range in severity and often go undiagnosed and untreated [8][9][10][11]. Major Depressive Disorder (MDD) disproportionally affects women aged 20 -44, coinciding with the prime reproductive years and underscoring the importance of identifying preventive and treatment modalities for PPD among this age group [12].…”
Section: Introductionmentioning
confidence: 99%
“…Our findings of a higher HPA-system sensitivity in more anxious individuals after HF-rTMS applied over the right DLPFC might be especially germane in light of the therapeutic applications of rTMS as a treatment for anxiety disorders and/or posttraumatic stress disorder (PTSD) (Cohen et al, 2004;Pallanti and Bernardi, 2009;Zwanzger et al, 2009;Handwerger, 2009;Yue et al, in press). Because of the overwhelming evidence that GABAergic mechanisms regulate neuroendocrine stress responses (Herman et al, 2002;Herman et al, 2004;Kovács et al, 2004;Cullinan et al 2008;Radley et al, 2009) and the importance of GABA receptor involvement in the pathophysiology and treatment of anxiety disorders (Lydiard, 2003;Nemeroff, 2003;Kalueff and Nutt., 2007), it is tempting to assume that in our study the observed HPA-axis sensitivity to one HF-rTMS session in more anxious females was mediated by the GABA system.…”
Section: Discussionmentioning
confidence: 99%
“…However both of these investigations assessed both early life stress and the psychiatric outcome many years after these experiences, introducing the potential for recall bias and limiting researchers' ability to prospectively examine psychobiological developmental processes in response to trauma. Additionally, although both depression and PTSD are stress-sensitive conditions characterized by alterations of the HPA axis, the patterns of HPA activity and reactivity found in PTSD diverge markedly from the patterns found in depression [24].…”
Section: Introductionmentioning
confidence: 99%